Answer:
1,560
it could be letter B
Step-by-step explanation:
I'm not sure about it but yeahh hope that helps
Answer:
4
Step-by-step explanation:
The y-variable can be eliminated by adding 3 times the first equation to the second:
3(2x -y) +(x +3y) = 3(11) +(-5)
7x = 28 . . . . simplify
x = 4 . . . . . . . divide by 7
_____
Using Cramer's Rule, you can also find the x-value. The math is not so different.
x = ((-1)(-5) -(3)(11))/(-1(1) -3(2)) = -28/-7 = 4
Answer:
17
Step-by-step explanation:
√25 = 5
√144 = 12
5 + 12 = 17
Please mark me Brainliest :)